1994
DOI: 10.2135/cropsci1994.0011183x003400010046x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Viability of Acremonium Endophytes in Tall Fescue and Meadow Fescue Plant Introductions

Abstract: Assessment of the infection status and viability of endophytic Acremonium spp. in USDA plant introductions (PI) of Festuca spp. would aid in identifying potentially desirable endophyte strains for improving pasture and turf species. The PI collection of tall fescue (F. arundinacea Schreb.) and meadow fescue (F. pratensis Huds.) was screened to determine Acremonium infection rate and viability. For tall fescue, 20 seed from each of 565 regenerated seedlots were microscopically examined for endophyte. Seventy‐ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Seven accessions were already known to be endophyte infected from previous studies, but when tested with the immunoblot they were negative. Moreover, Holder et al (1994) tested seeds of 198 meadow fescue accessions, only 30 of them were found to be E+ and they experienced the same phenomenon when assessing the infection status of the seedlings, realizing that infection rates were lower than the ones in the seeds. The loss of endophyte viability is a known problem related to seeds storage conditions which are optimized to preserve seeds’ germination rate rather than endophytes’ viability (Clement et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven accessions were already known to be endophyte infected from previous studies, but when tested with the immunoblot they were negative. Moreover, Holder et al (1994) tested seeds of 198 meadow fescue accessions, only 30 of them were found to be E+ and they experienced the same phenomenon when assessing the infection status of the seedlings, realizing that infection rates were lower than the ones in the seeds. The loss of endophyte viability is a known problem related to seeds storage conditions which are optimized to preserve seeds’ germination rate rather than endophytes’ viability (Clement et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation is the occurrence of imperfect vertical transmission to seeds (Ravel et al, 1997) or the loss of the endophyte viability in the seeds, which generates E- plants. Moreover, several commercially available varieties are infected with Epichloë endophytes although most of them are endophyte free (Holder et al, 1994; Saikkonen et al, 2000), and their extensive use might have affected the species composition and the ratio between infected and non-infected grasses in the area of sampling. According to our results in Sweden, Norway and on the Alps it is highly unlikely to find wild extensive habitats containing Epichloë -free meadow fescues.…”
Section: Discussionmentioning
confidence: 99%
“…These microorganisms are solely vertically transmitted from the mother plant to the seeds (Siegel et al 1984;Philipson and Christey 1986). This vertical transmission process can be imperfect, in part because a variable amount of the seeds produced by infected plants can remain uninfected (Holder et al 1994;Welty et al 1994;Hill et al 2005;Wheatley et al 2007). Further, endophyte viability in relation to the host seed has been well documented in Festuca arundinacea and Lolium perenne (Rolston et al 1986;Welty et al 1987;Wheatley et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although this method does not necessarily provide a direct estimate of the frequency of infected vs. uninfected plants, it does estimate the relative biomass or cover of infected plants. Surveys of endophyte-infection frequency have been conducted also in other regions and with other grass species, and they demonstrate similar variability in infection frequencies (42)(43)(44)(45)(46)(47)(48)(49).…”
mentioning
confidence: 99%